Multidisciplinary approach to pelvic leiomyomatosis with intracaval and intracardiac extension: A case report and review of the literature - Nnamdi I. Gwacham; Madhavi Manyam; Christine K. Fitzsimmons; Karolina A. Kilowski; David Varnagy; Tomer Z. Karas; Robert W. Holloway (Elsevier, 2022)
Intravenous leiomyomatosis (IVL) is an uncommon variant of leiomyoma characterized by intravascular proliferation of a histologically benign smooth muscle tumor extending beyond the uterus into the distant great vessels. Leiomyomatosis may reach the inferior vena cava, right atrium, and pulmonary arteries. Owing to its rare occurrence, intracardiac leiomyomatosis has been reported as isolated case reports and small case series. Early diagnosis and prompt surgical intervention are vital to prevent cardiac symptoms, pulmonary embolism, and sudden death. Complete tumor resection is essential for a favorable outcome, usually assisted with multimodal surgical imaging and multidisciplinary surgical planning. Herein, we report the case of a 50-year-old female that presented with a three-month history of abdominal pain and lower extremity edema with evidence of IVL extending to the inferior vena cava and right atrium. The patient was managed with a single-stage surgery involving cardiopulmonary bypass and excision of the right atrial and inferior vena cava tumors, as well as modified radical total abdominal hysterectomy and bilateral salpingo-oophorectomy.